2016
DOI: 10.18632/oncotarget.12255
|View full text |Cite
|
Sign up to set email alerts
|

The precision relationships between eight GWAS-identified genetic variants and breast cancer in a Chinese population

Abstract: Some of the new breast cancer susceptibility loci discovered in recent Genome-wide association studies (GWASs) have not been confirmed in Chinese populations. To determine whether eight novel Single-Nucleotide Polymorphisms (SNPs) have associations with breast cancer risk in women from southeast China, we conducted a case-control study of 1,156 breast cancer patients and 1,256 healthy controls. We first validated that the SNPs rs12922061, rs2290203, and rs2981578 were associated with overall breast cancer risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Many recent studies have established that genetic factor also had a vital role in progression of breast cancer (Bray et al 2013;Sehrawat et al 2011;Ruiz-Narvaez et al 2013;Han et al 2011), and there were 27% of the breast cancer risk influenced by genetic variants (Lichtenstein et al 2000). In addition, a number of genes including BRCA1, BRCA2, PTEN, TP53, CYP17 and other different genes have demonstrated that their polymorphisms were associated with risk of breast cancer (Nelson et al 2012;Liao et al 2018;Walsh and King 2007;Han et al 2016a;Wang et al 2016;Lilyquist et al 2018;He et al 2014;Chen et al 2016b;Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have established that genetic factor also had a vital role in progression of breast cancer (Bray et al 2013;Sehrawat et al 2011;Ruiz-Narvaez et al 2013;Han et al 2011), and there were 27% of the breast cancer risk influenced by genetic variants (Lichtenstein et al 2000). In addition, a number of genes including BRCA1, BRCA2, PTEN, TP53, CYP17 and other different genes have demonstrated that their polymorphisms were associated with risk of breast cancer (Nelson et al 2012;Liao et al 2018;Walsh and King 2007;Han et al 2016a;Wang et al 2016;Lilyquist et al 2018;He et al 2014;Chen et al 2016b;Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiology studies have demonstrated that age, obesity, menstrual status, positive family history and previous benign breast disease are correlated with the development of breast cancer [ 5 10 ]. Whereas accumulative evidences have revealed that, some genetic variants such as single nucleotide polymorphisms (SNPs) in tumor suppressor genes or oncogenes, could also play a critical role in the genetic susceptibility to breast cancer [ 11 17 ]. Although a great proportion of publications have focused on the cancer-related polymorphisms that are located in protein-coding genes, several SNPs located in chromosomal regions which do not encode genes are also indicated to contribute to the risk of different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…We confirmed the previous findings of the GWAS from Japan and China, showing that there was an association between BC risk and a locus in the LOC643714 region. 17,19 In our study, we found a significant difference of rs12922061 genotype distribution in postmenopausal and premenopausal patients under the dominant model (OR=3.158; 95% CI 1.410, 7.073, statistical power=82%), and the over-dominant model (OR= 2.629; 95% CI 1.170, 5.907; statistical power=76%).…”
Section: Discussionmentioning
confidence: 47%